A Review on Educational Status of Scheduled Tribes of Rajasthan - Rana, Suman; Devi, Wairokpam Premi (JOURNAL OF INDIAN EDUCATION, 2017)
Scheduled Tribes are geographically secluded, socio-economically isolated and marginalised communities of India. They are often illiterate or less educated despite several efforts from the government through programmes/schemes. The policymakers’ little attention to ST population has led to high school dropout rates and consequently, it has directly impacted the overall educational status of the tribals. The main objective of the study was to identify the educational status of ST population in the State of Rajasthan. The present study is based on government reports, i.e., Census of 2011; Statistical Profile of Scheduled Tribes 2013; All India Survey on Higher Education (2011–12); Educational Statistics at a Glance 2016; Educational Status Report Rajasthan; Secondary Education in India Progress towards Universalisation; and School Education in India (U-DISE) and it is meta-analytical in nature. This study, though limited in scope, clarifies the educational status of ST population in Rajasthan. It presents comparative analysis of the available data on ST population of Rajasthan with the total population of India. A critical scrutiny of the data revealed that inspite of high enrolment in all levels of education, the literacy is quiet low in comparison to the other categories. They have even the lowest transition rate from primary to upper primary level and secondary to higher secondary level of education. The dropout rate is also high among them. Despite several Central and State government initiatives for ST population, the tribal groups still remain unreached and vulnerable.